Anticipation of the issues concering "dispute" in statutory adjudication under CIPAA 2009 in Malaysia - Tay, Joanna Yuan Ju, 1988-; Nur Emma Mustaffa, supervisor; Fakulti Alam Bina (2011)
Project Paper (Sarjana Muda Ukur Bahan)) - Universiti Teknologi Malaysia, 2011